2017
DOI: 10.1371/journal.pntd.0005743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new multiplex real-time PCR with the Kato Katz thick smear and copro-antigen ELISA for the detection and differentiation of Taenia spp. in human stools

Abstract: BackgroundTaenia solium, the cause of neurocysticercosis (NCC), has significant socioeconomic impacts on communities in developing countries. This disease, along with taeniasis is estimated to infect 2.5 to 5 million people globally. Control of T. solium NCC necessitates accurate diagnosis and treatment of T. solium taeniasis carriers. In areas where all three species of Taenia tapeworms (T. solium, Taenia saginata and Taenia asiatica) occur sympatrically, conventional microscope- and copro-antigen based diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…following DNA sequencing. The methods and results have been described and published elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…following DNA sequencing. The methods and results have been described and published elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Dak Lak province, there is no information available on the infection status of T. saginata in livestock, however our research data on the seroprevalence of cysticercosis in pigs was 0.95% [ 13 ]. A previous study carried out by our group using a newly developed multiplex real-time PCR found the prevalence of Taenia solium, T. saginata and T. asiatica taeniasis to be 1.2%, 5.8% and 1.5%, respectively in Dak Lak province [ 14 ]. In this study, our aims were to: i) estimate the seroprevalence of T. solium cysticerci exposure using the lentil-lectin purified glycoprotein enzyme-linked immunoelectrotransfer blot (LLGP-EITB) assay; ii) identify and quantify risk factors for human T. solium cysticerci exposure and taeniasis ( Taenia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Within the province, three districts namely Buon Don, Krong Nang and M’Drak were chosen as the study sites based on their diverse geographic characteristics ( Fig 1 ). The characteristics of these districts have been described in detail elsewhere [ 22 ]. A sampling frame listing the name of all villages in Dak Lak province was obtained from Sub-Department of Animal Health office within the Ministry of Agriculture and Rural Development.…”
Section: Methodsmentioning
confidence: 99%
“… The black shaded areas show the study locations in Buon Don, Krong Nang and M’Drak districts. This figure was adapted from Ng-Nguyen et al (2017) [ 22 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation